The Impact of Integrating Discovery Learning and Differentiated Instruction on Students’ Critical Thinking Skills in Heat and Temperature Topics - Trihartini, Trihartini; Nurohman, Sabar; Buhera, Rusdiman (Department of Physics Education, Universitas Mataram, 2025)
Critical thinking is essential in contemporary times as it trains students to analyze, evaluate, and make logical and reflective decisions. This study aimed to determine the effect of discovery learning integrated with differentiated instruction on students' critical thinking skills. This research employed a pre-experimental method with a one-group pretest-posttest design. The research subjects were 30 ninth-grade students of SMPN 4 Sentajo Raya. Data were collected through pretest and posttest assessments using critical thinking questions on temperature and heat. The results showed that the average pretest score was 48 and the posttest score was 78. Based on the paired samples test with a significance value (2-tailed) < 0.05, the null hypothesis (H₀) was rejected and the alternative hypothesis (H₁) was accepted. This indicates a significant difference in students' critical thinking skills before and after implementing the discovery learning integrated with differentiated instruction.